A preliminary investigation of caramelisation and isomerisation of allulose at medium temperatures and alkaline pHs: a comparison study with other monosaccharides. (30th May 2021) - Ertugrul, Ulku; Tas, Ozan; Namli, Serap; Oztop, Mecit H.
Summary: Allulose, also known as rare sugar, is a very reactive monosaccharide in browning reactions. In this study, the caramelisation of allulose was investigated for the first time. To study caramelisation, sugar solutions (glucose, fructose and allulose) were prepared with distilled water and buffer solutions at pH 7, 10, 12 and were freeze‐dried afterwards. To let caramelisation occur, samples were incubated at 55% relative humidity (RH) and 50 °C. Results showed that samples prepared with pH 10 and pH 12 buffer solutions resulted in a higher browning rate than samples prepared with distilled water (DW) and pH 7 buffer solution. Moreover, according to HPLC and total reducing sugar content results, allulose ( Allu ) samples had the lowest remaining reducing sugar (RRS) amount, indicating that Allu samples depleted more in the reaction. Overall, the approach followed in this study can be considered as a novel strategy to obtain allulose‐containing caramel‐like products more efficiently than conventional methods. Abstract : Conventional caramelisation (~ 150 °C) usually requires high temperature treatment for the sugars. In this study, we performed caramelisation of glucose, fructose, and allulose at medium temperatures (~ 50 °C) and alkali pH as an alternative approach to the conventional caramelisation.